Trigonometry

Asked by  | 30th Sep, 2009, 10:58: PM

Expert Answer:

[(sinA + cosA)/(sinA - cosA)] + [(sinA - cosA)/(sinA + cosA)]

= [(sinA + cosA)2 + (sinA - cosA)2]/(sin2A - cos2A)

= 2/(sin2A - cos2A) .................Using (a ± b)2 = a2 ± 2ab + b2

Dividing numerator and denominator by cos2A

= 2sec2A/(tan2A - 1)

Regards,

Team,

TopperLearning.

 

Answered by  | 30th Sep, 2009, 11:41: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.